Utilizing the Optimization Algorithm in Cascaded H-Bridge Multilevel Inverter - M.Suresh Kumar; Ramani Kannan (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper proposed the elimination of undesired harmonic in a Cascaded H-Bridge Multi-Level Inverter by using Selective Harmonic Elimination-Pulse Width Modulation strategy with programmed Particle Swarm Optimization algorithm. In Selective Harmonic Elimination Pulse Width Modulation technique, PSO algorithim is used to determine the non-linear transcendental equation to precise obligatory switching angles for eliminate low order harmonics and reduce the Total Harmonic Distortion from the inverter output voltage waveform while maintaining the required fundamental voltage at the desired value. Computational results are validate that the proposed method does competently eliminate the low order harmonics and also resulted in minimum Total Harmonic Distortion value. The results exposed that the proposed method can achieve efficaciously to the optimal solution more rapidly than other algorithms. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7132